2020
DOI: 10.1097/inf.0000000000002727
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of an MF59-adjuvanted Quadrivalent Seasonal Influenza Vaccine in Young Children at High Risk of Influenza-associated Complications: A Phase III, Randomized, Observer-blind, Multicenter Clinical Trial

Abstract: Background: Vaccination against seasonal influenza is recommended for all children with a history of medical conditions placing them at increased risk of influenza-associated complications. The immunogenicity and efficacy of conventional influenza vaccines among young children are suboptimal; one strategy to enhance these is adjuvantation. We present immunogenicity and safety data for an MF59-adjuvanted quadrivalent influenza vaccine (aIIV4) in healthy children and those at a high risk of influenza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…MF59 adjuvant increased influenza vaccine efficacy from 43 to 89% in young children 40 and is an effective adjuvant for influenza vaccines in this population 41 . Phase III studies of MF59 quadrivalent seasonal influenza vaccines in young children have been completed in Europe 42 and are ongoing in the US (ClinicalTrials.gov Identifier: NCT01346592 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…MF59 adjuvant increased influenza vaccine efficacy from 43 to 89% in young children 40 and is an effective adjuvant for influenza vaccines in this population 41 . Phase III studies of MF59 quadrivalent seasonal influenza vaccines in young children have been completed in Europe 42 and are ongoing in the US (ClinicalTrials.gov Identifier: NCT01346592 43 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, because vaccine adjuvants enhance antigen recognition by host APCs, such as DCs, and thus contribute to the effective induction of protective acquired immunity [ 59 , 60 , 61 ], the development of vaccines for children must include appropriate adjuvants that efficiently activate the immature immune system. To date, various adjuvants (e.g., alum, chitosan, and MF59) have been developed and used in mice and humans [ 62 , 63 , 64 , 65 , 66 , 67 ], and some of them were tested in children [ 64 , 66 , 67 ]. Alum, salts of aluminum, is the classical adjuvant most often used in vaccines in humans.…”
Section: Infant Immune Development and Its Impact On Vaccine Respomentioning
confidence: 99%
“…MF59, a potent oil-in-water emulsion, has been developed and used as adjuvant for influenza vaccine and its safety and effectiveness confirmed in adult [ 65 ]. Recent studies also demonstrated that MF59 is effective and safe in young children 6–35 months as influenza vaccine adjuvant [ 66 , 67 ], whereas it needs further confirmation whether MF59 is safe and effective in children as a potent universal adjuvant for other vaccine antigens.…”
Section: Infant Immune Development and Its Impact On Vaccine Respomentioning
confidence: 99%